Youth in agribusiness: Shaping the future of agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2017)
More than 1 billion young people (aged 15–24 years) live in developing countries. Africa’s youth population expected to double to over 830 million by 2050, and 10-12 million youth enter the workforce each year in Africa. However, there are scant employment and entrepreneurial opportunities for young women and men. Creating jobs for these young people requires urgent government intervention at the policy level